From Goldilocks to twin peaks: multiple optimal regimes for quantum transport in disordered networks. Issue 14 (28th March 2023) - Coates, Alexandre R.; Lovett, Brendon W.; Gauger, Erik M.
Abstract : Physically modelled molecular transport networks can have more than one regime of environment coupling that optimises their steady state transport efficiency. Abstract : Understanding energy transport in quantum systems is crucial for an understanding of light-harvesting in nature, and for the creation of new quantum technologies. Open quantum systems theory has been successfully applied to predict the existence of environmental noise-assisted quantum transport (ENAQT) as a widespread phenomenon occurring in biological and artificial systems. That work has been primarily focused on several 'canonical' structures, from simple chains, rings and crystals of varying dimensions, to well-studied light-harvesting complexes. Studying those particular systems has produced specific assumptions about ENAQT, including the notion of a single, ideal, range of environmental coupling rates that improve energy transport. In this paper we show that a consistent subset of physically modelled transport networks can have at least two ENAQT peaks in their steady state transport efficiency.